2022
DOI: 10.1186/s40168-021-01206-7
|View full text |Cite
|
Sign up to set email alerts
|

Species-targeted sorting and cultivation of commensal bacteria from the gut microbiome using flow cytometry under anaerobic conditions

Abstract: Background There is a growing interest in using gut commensal bacteria as “next generation” probiotics. However, this approach is still hampered by the fact that there are few or no strains available for specific species that are difficult to cultivate. Our objective was to adapt flow cytometry and cell sorting to be able to detect, separate, isolate, and cultivate new strains of commensal species from fecal material. We focused on the extremely oxygen sensitive (EOS) species Faecalibacterium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 78 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…We also observed that Faecalibacterium could not grow as a monoculture in GAM but that it was abundantly detected in co‐culture. Regarding monocultures, previous results indicated that Faecalibacterium growth was strongly stimulated in the presence of acetate 35 or that it could grow in GAM supplemented with bovine rumen, cellobiose, and inulin 36 . These findings indicate that this bacterium benefits from interaction with other bacteria included in the synthetic gut microbial consortium.…”
Section: Resultsmentioning
confidence: 91%
“…We also observed that Faecalibacterium could not grow as a monoculture in GAM but that it was abundantly detected in co‐culture. Regarding monocultures, previous results indicated that Faecalibacterium growth was strongly stimulated in the presence of acetate 35 or that it could grow in GAM supplemented with bovine rumen, cellobiose, and inulin 36 . These findings indicate that this bacterium benefits from interaction with other bacteria included in the synthetic gut microbial consortium.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, we postulate that such methodologies could be implemented in standard microbiology laboratories. This is a remarkable advantage compared with methods using fluorescence-activated cell sorting, some of which have already been reported in the literature ( 46 ). Second, our method allows the study of host-microbiota interactions from a completely new perspective: by depleting/enriching specific populations in the microbiota, we can infer their role within the community.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, we established an integrated low-cost method compared with Raman-activated cell sorting [ 34 ] and flow cytometry [ 35 ] that allowed for the enrichment and isolation of rumen ureolytic bacteria. This method allowed for the enrichment of ureolytic bacteria, embedding and then allowing the growth of single bacterial cells in agarose microspheres, selection of those that carry urease genes (the bacteria of our interest), and incubation of the selected urease gene-carrying individual strains in dialysis bags placed in rumen-simulating conditions.…”
Section: Discussionmentioning
confidence: 99%